Men Who Have Sex With Men With Mycoplasma genitalium–Positive Nongonococcal Urethritis Are More Likely to Have Macrolide-Resistant Strains Than Men With Only Female Partners: A Prospective Study. Issue 8 (August 2019) - McIver, Ruthy; Jalocon, Dean; McNulty, Anna; Jeoffreys, Neisha J.; Chen, Sharon Chih-Ann; Power, Melissa; Couldwell, Deborah Leone
Abstract : Background: Mycoplasma genitalium was previously less common among men who have sex with men (MSM) compared with men with only female partners (MSW) in men with nongonococcal urethritis (NGU) in Sydney, Australia. We aimed to determine the prevalence of M. genitalium and of macrolide-resistant M. genitalium in men with NGU and to compare differences between prevalence and resistance rates between MSM and MSW. Methods: We enrolled 588 men with NGU in a prospective study at two urban sexual health services. The ResistancePlus MG assay (SpeeDx, Australia) was used to detect both M. genitalium, and macrolide resistance-associated mutations in first-void urine samples. Demographic, behavioral and clinical data were analyzed to investigate associations with M. genitalium infection or the presence of macrolide resistance. Results: Mycoplasma genitalium prevalence was 12.8% (75 of 588) overall and among MSM (12.8% [39 of 306]) and MSW (12.8% [36 of 282]; risk ratio [RR], 1.00; 95% confidence interval [CI], 0.65–1.52). Overall, 70.7% (53 of 75) of M. genitalium strains were macrolide-resistant, with significantly more resistance among MSM (89.7%, 35 of 39) than MSW (50%, 18 of 36) (RR, 1.80; 95% CI, 1.27–2.54; P = 0.001). On multivariate analysis, the presence of M. genitalium macrolide resistance mutations was independently associated with having male sexual partners compared with having only female partners (RR, 1.55; 95% CI, 1.02–2.38; P = 0.042). Conclusions: Prevalence of M. genitalium among men with NGU is now similar for MSW and MSM and has increased locally from 5.2% to 12.8% within the last 10 years. Men who have sex with men are significantly more likely than MSW to harbor macrolide-resistant M. genitalium infections. This has treatment implications. Abstract : In a prospective study of men with nongonococcal urethritis in Sydney, among men with Mycoplasma genitalium infection, men with male sexual partners were significantly more likely than men with female partners to harbor macrolide-resistant infections.